2019
DOI: 10.4236/gep.2019.78008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Atlantic Multidecadal Oscillation and the Pacific Decadal Oscillation on Global Temperature by Wavelet-Based Multifractal Analysis

Abstract: Oceanic-atmospheric patterns, Atlantic Multidecadal Oscillation (AMO) and Pacific Decadal Oscillation (PDO), and their respective influence on the global warming hiatus were the main interests of this study. In general, a fractal property is observed in the time series of dynamics of complex systems; hence, we investigated the relations among the AMO, PDO, and El Niño-Southern Oscillation (ENSO) from the point of view of multifractality, in which changes in fractality were detected with multifractal analysis u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…SAT is a component of SATDs, so the global warming should affect the SATDs. Previous research have found the global warming hiatus during 1951-1976and 1998(Kosaka and Xie 2013Maruyama 2019). It denotes the fluctuations in global cooling or warming at a decadal scale.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…SAT is a component of SATDs, so the global warming should affect the SATDs. Previous research have found the global warming hiatus during 1951-1976and 1998(Kosaka and Xie 2013Maruyama 2019). It denotes the fluctuations in global cooling or warming at a decadal scale.…”
Section: Conclusion and Discussionmentioning
confidence: 99%